Study of Pre and Post Supplementation Green Tea Extracts to MDA Levels - Goenawan, Hanna; Lesmana, Ronny; Huda, Fathul; Baniasih, Akbar I.; Farenia, Reni; Purba, Ambrosius (Indonesian Journal of Clinical Pharmacy, 2013)
High intensity exercise (HI) induces oxidative stress. Running for 2400 meters is one of the simple exercise form which can be counted as HI. During HI, increase of oxygen consumption happened in muscle cell resulted in an increase of oxidant level. The aim of the study was to measure the effects of Indonesian green tea supplementation, before and after HI to the level of lipid peroxidation (TBARSMalonyldialdehyde (MDA)). The subjects of study were 42 male students from Faculty of Medicine, Universitas Padjadjaran (FMUP) and Faculty of Physical Exercise, Indonesia University of Education (FPOK-UPI). The subjects were divided into trained and untrained subject. Subjects were divided into groups using Astrand Harvard step test. The purpose of this test was measuring the level of VO2 max. Blood samples for MDA level were collected at 3 hours before and after high intensity aerobicÂ  exercise. Oxidative stress was induced by 2400 meters run. The result showed that green tea supplement-ation was effective to decrease MDA plasma level especially after exercise. Green tea could serve as natural antioxidant resources, which potentially can be used as potential sport supplemental drink.Key words: Aerobic exercise, Malonyldialdehyde (MDA), pre and post exerciseStudi Pra dan Pasca Pemberian Suplemen Ekstrak Teh Hijauterhadap Kadar MDAHigh intensity exercise (HI) dapat menginduksi stres oksidatif. Berlari sejauh 2400 meter merupakan salah satu bentuk latihan sederhana yang dapat digolongkan sebagai HI. Selama HI, konsumsi oksigen pada sel otot meningkat yang dapat menyebabkan peningkatan kadar oksidan. Penelitian ini bertujuanuntuk mengukur efek dari suplemen teh hijau Indonesia sebelum dan setelah HI terhadap kadar lipid peroksida (TBARS-Malonyldialdehyde (MDA)). Subjek penelitian ini adalah 42 mahasiswa laki-laki dari Fakultas Kedokteran Universitas Padjadjaran dan Fakultas Pendidikan Olahraga dan Kesehatan,Universitas Pendidikan Indonesia. Subjek penelitian dibagi ke dalam kelompok terlatih dan tidak terlatih dengan menggunakan cara pengujian Astrand Harvard. Tes ini bertujuan untuk mengukur kadar VO2 max. Sampel darah untuk kadar MDA diambil 3 jam sebelum dan setelah high intensity aerobic exercise. Stres oksidatif diinduksi dengan berlari sejauh 2400 meter. Hasil penelitian menunjukkan bahwa suplemen teh hijau efektif dalam menurunkan kadar MDA dalam plasma khususnya setelah berlari. Teh hijau dapat menjadi sumber antioksidan alami yang berpotensi sebagai minuman suplemen olahraga.Kata kunci: Aerobic exercise, Malonyldialdehyde (MDA), sebelum dan setelah berlari